Education Building Maintenance Priority Strategy Consider Safety Condition Using Analytical Hierarchy Process (AHP) - Arifin, Muhammad Faizal Ardhiansyah; Aditya, Yoga; Budiwirawan, Agung; Sutarto, Agung; Taveriyanto, Arie (Jurnal Teknik Sipil dan Perencanaan, 2022)
Abstract. Buildings with component degradation are a common challenge for all construction companies across the world. There are various building's components that it is challenging for construction companies to manage them all at once. It was not considered that the building agency is responsible for more than one building at a time. These issues have gotten more complicated as a result of the building agencies' limited financial resources for building maintenance. This study attempts to provide a visible solution to manage the building maintenance strategy based on complex building maintenance problems. The Analytical Hierarchy Process was used to give a complete way for assessing the building's condition (AHP). This method developed in this study was applied to define the building condition and followed by determining the building priority to be maintained. The building component in this study was specified into three specific components such as interior, exterior, and building utility. To complete this method, a three-level priority factor was determined with consideration from the safety factor follow by the functionality factor, dan the last is an esthetic factor. The developed model shows a proper and reliable solution related to the degradation of building components and their functionalities.